Impacts of Smoking on Health and Social Status: A Case of Makawanpur District, Nepal - Adhikari, Ram Prasad; Upadhyaya, Shankar Prasad; Adhikari, Bhashkar Chandra; Koirala, Muna; Hatuwal, Muna; Lamichhane, Sita (International Research Journal of MMC, 2024)
The goal of the study was to analyze the psycho-social impacts of smoking on health and social status. The study was conducted in the Hetauda Sub-Metropolitan City of Makawanpur district, Nepal. Out of 19 wards, 5 were selected by simple random sampling technique for the study and the data were taken with 200 respondents from 5 wards. A structured survey questionnaire was administered to collect the data. The data were collected from February 2024 to March 2024. There was a significant association between the gender of respondents and the frequency of smoking (p=0.011), between the gender of the respondents and causes of smoking (p=0.003), and between the gender of the respondents and encouraging friend circle for smoking (p=0.000). Smoking habit is not only bad for health, but it causes social disparities, loss of prestige, and various psychological problems also. So, awareness to the illiterate and counselling for the literate people is sought necessary. The study helps health organizations to form the plan and policy against smoking and it also helps the government to form a policy for unemployed people and create new job opportunities for youths.